Insights into fabrication mechanism of pure copper thin wall components by selective infrared laser melting. Issue 8 (9th September 2019) - Guan, Jieren; Zhang, Xiaowei; Jiang, Yehua; Yan, Yongnian
Abstract : Purpose: This study aims to obtain the mechanistic insights for the fabrication of pure copper thin wall components by selective infrared (IR) laser melting (SLM) and correlated with microstructure development, microhardness, surface morphology and phase analysis. Experimental processes for single track and selection of substrate materials have been studied using a combination of different laser powers and scanning speeds. Design/methodology/approach: SLM of pure copper was performed on a YONGNIAN Laser YLMS-120 SLM machine using an Nd: YAG fiber laser operating at 1, 060 nm in the NIR region. Single-track experiments and processing parameters are investigated through different combinations of laser power and scanning speed. The microstructure of the fabricated pure copper samples by SLM technique was analyzed by means of X-ray diffraction, scanning electron microscope equipped with energy disperse spectrometer, optical microscope (OM) and micro-hardness tester. Findings: Steel-based substrates were found suitable for pure copper manufacturing due to sufficient heat accumulation. The width of a single track was determined by liner energy density, showing discontinuities and irregular morphologies at low laser powers and high scanning speeds. As a result of instability of the molten pool induced by Marangoni convection, cracks and cavities were observed to appear along grain boundaries in the microstructure. The top surface morphology of SLM-processed component showed a streamflow structure and irregular shapes. However, the powder particles attached to side surface, which manifest copper powders, are even more sensitive to melt pool of contour track. The crystal phase characteristics of copper components indicated increasing crystallite size of a-Cu, and the decreasing intensity of diffraction peak was attributed to the presence of defects during SLM. The maximum relative density and microhardness were 82 per cent and 61.48 HV0.2, respectively. The minimum thickness of a pure copper thin wall component was 0.2 mm. Originality/value: This paper demonstrated the forming mechanism and explored feasibility of pure copper thin wall parts by SLM technology in the NIR region. The surface morphology, microstructure and crystal structure were preliminary studied with laser processing parameters.